The impact of market participants' interaction on futures prices: comparing three US wheat futures markets. (2017) - Bosch, David
The extreme price movements in the three US wheat futures markets in 2008 and 2011 can be largely explained by fundamental developments. But different price reactions in those wheat futures markets raise doubt whether only supply and demand moved wheat futures prices. The question arises whether the different behaviour of market participants is also essential for price discovery. This study examines the influence of different market structures on prices of the three most important US wheat futures markets. For this purpose, trader's positions of the disaggregated commitments of traders (DCoT) report from June 2006 to December 2013 are analysed. Results reveal that during the price peak, the behaviour of hedgers and other market participants at the Minneapolis Grain Exchange contributed to the decoupling of wheat futures prices from the fundamental development. This demonstrates that market structure is of great importance for price development in futures markets.